Inverse design of cellular structures with the geometry of triply periodic minimal surfaces using generative artificial intelligence algorithms - Li, Zhou; Li, Junhao; Tian, Jiahao; Xia, Shiqi; Li, Kai; Li, Maojun; Lu, Yao; Ren, Mengyuan; Jiang, Zhengyi (Elsevier, 2024)
Triply periodic minimal surfaces (TPMS) exhibit excellent mechanical and energy absorption properties due to their structural advantages. However, existing porous TPMS structural design methods are constrained to a forward process from structural parameters to mechanical properties. This study proposed an inverse design method that combines bidirectional generative adversarial networks (BiGAN) and mechanical performance targets, resulting in a combined TPMS structure of Primitive and IWP types with superior buffering and energy absorption capabilities. The results show that under a single load value target condition of the designed structure, the minimum deviation index (R2) between the load value corresponding to the displacement point and the target load value is only 0.987, and the maximum mean absolute percentage error (MAPE) is only 5.92 %. When considering the elastic modulus target, the approach successfully conducts two sets of combined structural designs meeting the requirements of both high and low elastic moduli. When targeting the specified load-displacement curve conditions, specifically when combining high elastic modulus with ascending plasticity, the designed structures exhibit an error of only 2.2 % compared to the target property. Moreover, the quasi-static uniaxial compression experiments conducted on additively manufactured designed structures confirm that the experimental curves match the target curves in terms of deformation trends and load value ranges. The success of this inverse design approach for cellular TPMS structures has the potential to expedite new structural material development processes.
Keywords: Triply periodic minimal surface; Generative artificial intelligence algorithms; Additive manufacturing; Inverse design; Numerical simulation; 4005 Civil Engineering; 40 Engineering; 4016 Materials Engineering; 7 Affordable and Clean Energy